Prognostic model of rapid hepatic fibrosis progression in men with chronic hepatitis C - T. I. Koval; L. M. Syzova; H. M. Dubynska; N. O. Pryimenko; S. S. Rudenko (Patologìâ)
The aim of the research was to determine clinical and genetic predictors and to create a prognostic model for the rapid hepatic fibrosis progression in men with chronic hepatitis C.